Specific Responsivity: An Assessment of the Effect of Verbal and Math Cognitive Abilities on the Completion of Prison Programs. Issue 2 (14th March 2020) - Silver, Ian A.; Nedelec, Joseph L.; Pompoco, Amanda
ABSTRACT: The risk, need and responsivity (RNR) model has emerged as an influential factor in the paradigm shift experienced by the American correctional system. Apparent by the existing literature, scholarship assessing the RNR model has rarely focused on the potential association between verbal and math cognitive abilities (CA) and the capacity for completing prison programming. The current study examined if offenders' CA influenced treatment completion. The data for the current study was derived from the Evaluation of Ohio's Prison Programs, which contains information on every individual incarcerated in the state of Ohio between 2008 and 2012. Overall, the results provided mixed support for CA as a specific responsivity factor. Theoretical and policy implications as well as study limitations are discussed.